Respuesta :
Answer: (-4, 3)
============================================================
Explanation:
Starting at (4, -1) and moving four units up will have us arrive at (4, 3). We add 4 to the y coordinate and keep the x coordinate the same. The algebraic rule is stated as [tex](x,y) \to (x,y+4)[/tex].
Next, we reflect over the y axis. This will have us flip the sign of the x coordinate while keeping the y coordinate the same. The algebraic rule for this kind of reflection is [tex](x,y) \to (-x,y)[/tex]. The point (4,3) reflects over the y axis to get to (-4,3)
So we started at (4, -1), then moved four units up to get to (4,3) and then reflected over the y axis to get to (-4, 3) which is the final stop.
This is all shown in the diagram below.